Bacteriostatic and bactericidal activities of Andrographis paniculata extracts on skin disease causing pathogenic bacteria - Ahmed, Qamar Uddin; Sule, Abubakar; Abd. Samah, Othman; Omar, Muhammad Nor (Academic Journals, 2011)
Non-polar (dichloromethane) and polar (MeOH and aqueous) extracts of Andrographis paniculata(whole plant) were evaluated for in vitro antibacterial activity against 10 skin disease causing bacterial strains (6 gram positive strains; Staphylococcus saprophyticus, Staphylococcus epidermis, Staphylococcus aureus, Streptococcus pyogenes, Bacillus anthracis, Micrococcus luteus) and 4 gram negative strains (Proteus mirabilis, Proteus vulgaris, Neisseria meningitis, Pseudomonas aeruginosa) using disc diffusion method at three different concentrations; 1000, 500 and 250 μg/disc respectively. The extracts showed significant antibacterial activities against both Gram-positive and Gram-negative bacterial strains tested. Highest significant antibacterial activity was exerted by the aqueous extract against M. luteus at 1000 μg/disc and the least activity was exhibited by the DCM extract against N. meningitis at 250 μg/disc. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) observed were between 150 to 300 μg/ml and 250 to 400 μg/ml respectively, depending on microorganism and the nature of various extracts. Time-kill experiments indicated that A. paniculata extracts have bactericidal characteristic against most of the Gram positive bacteria and bacteriostatic activity against both Gram negative and Gram positive bacteria. These results candidly suggest the presence of promising antibacterial substances in the polar as well as non-polar extracts which could be the source of potential phytomedicine for the treatment of skin infections caused by the pathogenic bacterial strains. Our findings explicitly support its traditional claims and form a strong basis for further sincere efforts to explore A. paniculata’s antibacterial potential to treat skin frailties efficaciously.